Efficient narrow-band green nitride fluorescent material as well as preparation method and application thereof

By preparing the high-efficiency narrowband green nitride fluorescent material of Ba3-xEuxAl4Si3N10, the problem of lack of narrowband high-quantum efficiency fluorescent material emitting green light under excitation in the prior art is solved, and high-efficiency green light emission under excitation of 405 nm is achieved, which is suitable for white LED devices.

CN119592324AActive Publication Date: 2025-03-11XIAMEN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411871400.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

There is a lack of nitride fluorescent materials that can emit green light under excitation under the prior art, narrowband, and high quantum efficiency.

Method used

Using the chemical formula of Ba3-xEuxAl4Si3N10, a high-efficiency narrowband green nitride fluorescent material was prepared by performing high-temperature solid phase reactions under an ammonia pressure of 10 to 20 MPa.

Benefits of technology

Under the excitation of 405 nm of purple light, the main peak of the emission spectrum is located at 515-545 nm, the half-height width of the emission spectrum is 60-80 nm, and the quantum efficiency is >80%. It is suitable for white LED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592324A_ABST
    Figure CN119592324A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient narrow-band green nitride fluorescent material as well as a preparation method and application thereof, and relates to the field of fluorescent materials. The chemical formula of the fluorescent material is Ba (3-x) EuxAl4Si3N10, and x is more than 0 and less than or equal to 0.1. The crystal structure of a matrix corresponding to the fluorescent material belongs to an orthorhombic system, and the space group is Immm. Under excitation of 405 nm purple light, the main peak of the emission spectrum of the fluorescent material is 515-545 nm, the full width at half maximum of the emission spectrum is 60-80 nm, and the quantum efficiency is greater than 80%, so that the fluorescent material can be applied to white light LED devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fluorescent materials, and in particular to a high-efficiency narrow-band green nitride fluorescent material and a preparation method and application thereof. Background Art

[0002] White light LED light source is the most widely used lighting device today. The principle of achieving white light output is disclosed in patent document 1 (Song Kaixin, Jiang Jun, Li Wei, Qin Huibin, A fluorescent powder for white light LED and its preparation method, CN102295927A), which is to use LED to excite fluorescent materials, and the light emitted by the fluorescent materials under LED excitation and the light emitted by the LED that is not absorbed by the fluorescent materials are mixed to obtain white light. Obviously, fluorescent materials play a key role in white light LED light sources and determine the light, color and electrical quality of white light LED light sources to a certain extent.

[0003] Because fluorescent materials have advantages such as diversified structural characteristics, high luminous efficiency, good thermal stability and chemical stability, as disclosed in non-patent document 1 (Zhou Tianliang, Xie Rongjun, Research Progress of Nitrogen (Oxide) Fluorescent Powder, Functional Materials, 2014, 17, 17001-17011 / 6), nitride (oxygen) fluorescent materials occupy an important position in fluorescent materials for white light LEDs. Non-patent document 2 (Yang Zhigang, Synthesis of Rare Earth Doped M-Si-Al-ON Materials and Study on Their Luminescence Characteristics, Lanzhou University, Doctoral Dissertation, 2013) believes that in nitride (oxygen) and nitride oxide matrix materials, nitrogen has relatively small electronegativity and large electron cloud expansion effect, which can effectively promote the cracking of rare earth ion Sd energy level in the crystal field, reduce the energy level difference between 5d-4f, and cause the excitation and emission wavelengths to red shift. Therefore, generally speaking, pure nitrogen-containing nitride fluorescent materials mostly emit long-wavelength light (such as red light or deep red light), while oxynitride fluorescent materials containing both oxygen and nitrogen mostly emit short-wavelength light (such as green light and cyan light).

[0004] For example, for nitrogen oxides, Patent Document 2 (Yang Zhiping, Dong Xiuqin, Liu Shaopeng, Zhao Jinxin, A nitrogen oxide blue phosphor and its preparation method and application, CN106479498A) discloses a blue nitrogen oxide fluorescent material, whose chemical formula is Ba 1-x-y-z-m A1 x A2 y A3 zSi2O2N2:mEu, where A1 is at least one of Sr, Ca, Mg, Mn, Zn or Cu; A2 is at least one of Li, Na or K; A3 is at least one of Y, Sc, La, Ga, Gd or Lu; in the formula, 0 ≤ x ≤ 0.1, 0 ≤ y ≤ 0.1, 0 ≤ z ≤ 0.1, 0 < m < 0.2. This fluorescent material can be excited by ultraviolet-blue light, and its emission spectrum is located in the blue light region.

[0005] For example, for nitrogen oxides, Patent Document 3 (Zhang Liangliang, He Shuai, Zhang Jiahua, Zhang Xia, Hao Zhendong, Pan Guohui, Wu Huajun, Fluorescent-enhanced silicon-based nitrogen oxide cyan fluorescent powder and its preparation method, CN107722982A) discloses a cyan nitrogen oxide fluorescent material with a chemical general formula of (Ba 1-x-y-z-m M x R y A z )O·0.5SiO2·0.5Si3N4:mEu, where 0.01 ≤ m ≤ 0.05, 0 ≤ x ≤ 0.2, 0.005 ≤ y ≤ 0.2, 0.5 ≤ y / z ≤ 1, 0 < x + y + z < 0.5, R is at least one of La, Y, Tb, Dy, Ho, Er, Tm, Yb, Lu, Bi, Pr, Mn; M is at least one of Ca, Sr, Mg; A is at least one of K, Na, Li. This fluorescent material can be excited by blue light, and its emission spectrum is located in the cyan light region.

[0006] For example, for nitrogen oxides, Patent Document 4 (You Weixiong, Xiao Zongliang, Ye Xinyu, A nitrogen oxide green fluorescent powder and its preparation method, CN104774615A) discloses a green nitrogen oxide fluorescent material with a chemical general formula of (M 1-x Eu x )3Al 2-y Si y O 6-y N y , where M = one or several of Ca, Sr, Ba, 0 < x ≤ 0.1, 0.8 ≤ y ≤ 1.8. This fluorescent material can be excited by ultraviolet-blue light, and its emission spectrum is located in the green light region.

[0007] For example, for nitrogen oxides, Patent Document 5 (Jiao Huan, Wang Xiaoming, Zheng Hongwei, Yang Suya, Song Jianing, A broadband yellow-green emitting nitrogen oxide fluorescent powder and preparation method, CN114540015A) discloses a yellow-green nitrogen oxide fluorescent material with a chemical general formula of Ba 1-2x Si6N 8-y O y :xCe 3+ / xA +, where A represents one of Li, Na, K, Rb, and Cs; 0.005≤x≤0.1; 0<y≤2. The fluorescent material can be excited by light in the wavelength range of 200 to 480 nm, and the emission spectrum is in the yellow-green region.

[0008] For example, for nitrogen oxides, Patent Document 6 (Deng Degang, Xu Shiqing, Wang Huanping, Huang Lihui, Hua Youjie, Chai Wenxiang, Dai Jian, Huang Jun, A nitrogen oxide yellow phosphor for white light LED and its preparation method, CN105131944B) discloses a yellow nitrogen oxide fluorescent material, whose chemical formula is Li4Sr 1-x Ca(BO2N)2:xEu 2+ , wherein x is 0.001 to 0.10. The excitation band of the fluorescent material covers the ultraviolet and blue light regions, and the emission spectrum is located in the yellow light region.

[0009] Obviously, generally speaking, oxynitride fluorescent materials containing both oxygen and nitrogen mostly emit short-wavelength light (such as green light, cyan light).

[0010] For example, for nitrides, Patent Document 7 (Zhang Jiahua, Zhang Liangliang, Zhang Xia, Hao Zhendong, Nitride yellow phosphor based on blue light excitation and its application, CN102925152B) discloses a yellow nitride fluorescent material, whose chemical formula is (Sr 1-x-y-z M x L y Ce z )Al 1-y+z Si 4+y-z N7, wherein M is Ca or Ba, L is Li, Na or K, Ce is a trivalent cerium ion, x, y, z are element mole fractions, 0.01≤x≤0.1, 0.01≤z≤0.1, 0.1≤y / z≤0.99. The fluorescent material can be excited by ultraviolet light of 250 to 350 nm and blue light of 420 to 460 nm, and the emission spectrum is in the yellow light region of 550 to 565 nm.

[0011] For example, for nitrides, Patent Document 8 (Seto Takatoshi, Kijima Naoto, Phosphor and method for manufacturing the same, phosphor composition, light-emitting device, lighting device, image display device, and nitrogen-containing compound, CN101663372B) discloses an orange nitride fluorescent material, whose general chemical formula is R 3-x-y-z+w2 M z A 1.5x+y-w2 Si 6-w1-w2 Al w1+w2 O y+w1 N 11-y-w1, where R represents La, Gd, Lu, Y and / or Sc, M represents Ce, Eu, Mn, Yb, Pr and / or Tb, A represents Ba, Sr, Ca, Mg and / or Zn, 1 / 7≤(3-xy-z+w2) / 6<1 / 2, 0<(1.5x+y-w2) / 6<9 / 2, 0<x<3, 0≤y<2, 0<z<1, 0≤w1≤5, 0≤w2≤5, 0≤w1+w2≤5. Its representative chemical formula is La 2.15 Ce 0.10 Ca 1.23 Si6N 11 This fluorescent material can be excited by blue light, and its emission spectrum is located near 590 nm, which is the orange light region.

[0012] For example, for nitride, Patent Document 9 (Teng Xiaoming, He Jinhua, Liang Chao, Fu Yibing, Liu Kai, A nitride red phosphor and a preparation method thereof, CN102899038A) discloses a red nitride fluorescent material, whose chemical formula is L 2-x-y-z M5N8:Eu x / R y / R ′ z , wherein L is at least one of Ca, Sr or Ba; M is at least one of Si or Ge, wherein Si is essential; R is at least one of Na or K; R ′ is at least one of La, Sm or Sc; 0.001≤x≤0.5, 0.0001≤y≤0.01, 0.0001≤z≤0.01, and y=z. Its representative chemical formula is Ca 1.988 Si5N8: Eu 0.01 / Na 0.001 / La 0.001 This fluorescent material can be excited by blue light, and its emission spectrum is located near 620 nm, which is the positive red light region.

[0013] For example, for nitrides, Patent Document 10 (He Jinhua, Teng Xiaoming, Liang Chao, Fu Yibing, Aluminum nitride fluorescent material, preparation method, application and light-emitting device, CN102766455A) discloses a red nitride fluorescent material, whose chemical formula is L x SiAlN3:R y Eu 1-x-y , where 0.8≤x≤0.95, 0.01≤y≤0.18, L is selected from one or any combination of Ca and Sr, and R is selected from one or any combination of Cu and Mn. Its representative chemical formula is Ca 0.92 SiAlN3:Cu 0.04 Eu 0.06This fluorescent material can be excited by blue light, and its emission spectrum is located near 645 nm, which is the red light region.

[0014] For example, for nitrides, Patent Document 11 (Chao Kefu, Hu Dahai, Saqier, Ma Yizhi, Li Xiang, A Nitride Phosphor and Its Preparation Method, CN112126426A) discloses a deep red nitride fluorescent material, whose chemical formula (representative) is M3Al3N5:Ce, where M=Ca, Ba, Sr, Mg, or any combination of two. The fluorescent material can be excited by light with a wavelength range of 320 to 450 nm, and the emission spectrum is located near 670 nm, which is a deep red light region.

[0015] Obviously, generally speaking, most pure nitrogen-containing nitride fluorescent materials emit long-wavelength light (such as red light, or deep red light).

[0016] In addition, regarding the synthesis method of nitride fluorescent materials, non-patent document 3 (Liu Wenquan, Shi Ruixin, Duan Ruxia, Hu Gejile, Wu Wenjie, Chao Kefu, Bao Fuquan, Li Qi, Xin Yi, Tegus, Ca x Preparation of Ca by atmospheric pressure nitridation of Si alloy precursor 1-x AlSiN3:xEu red phosphor and luminescence properties, Journal of Luminescence, 2017, 38, 10:1295) believes that when alloy raw materials are used, nitride fluorescent materials can be prepared under more relatively mild conditions.

[0017] In short, there is still a lack of narrow-band, high-quantum-efficiency nitride fluorescent materials that can emit green light under violet light excitation. 3-x Eu x Al4Si3N 10 The high efficiency, narrow band, green light emitting behavior (0<x≤0.1, the crystal structure of the fluorescent material corresponding to the matrix belongs to the orthorhombic system, and the space group is Immm) is disclosed for the first time in the present invention. Summary of the invention

[0018] The purpose of the present invention is to solve the above problems in the prior art and provide a high-efficiency narrow-band green nitride fluorescent material and a preparation method thereof. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band green nitride fluorescent material is in the range of 515 to 545 nm, the half-width of the emission spectrum is in the range of 60 to 80 nm, and the quantum efficiency is greater than 80%.

[0019] To this end, a first object of the present invention is to provide a high-efficiency narrow-band green nitride fluorescent material.

[0020] A highly efficient narrow-band green nitride fluorescent material, the chemical formula of which can be expressed as:

[0021] Ba 3-x Eu x Al4Si3N 10

[0022] Among them, 0<x≤0.1.

[0023] Preferably, the x may be 0.05.

[0024] The second object of the present invention is to provide a method for preparing a highly efficient narrow-band green nitride fluorescent material. The method comprises the following steps: mixing a Ba precursor, a Eu precursor and an Al precursor, and performing a high-temperature solid-phase reaction in an atmosphere with an ammonia pressure of 10 to 20 MPa to obtain a highly efficient narrow-band green nitride fluorescent material.

[0025] Preferably, the Ba precursor is selected from BaSi alloy; the Eu precursor is selected from EuSi alloy; and the Al precursor is selected from AlN.

[0026] Preferably, in the Ba precursor, the molar ratio of Ba to Si is 1:1; in the Eu precursor, the molar ratio of Eu to Si is 1:1.

[0027] Preferably, the molar ratio of Ba, Eu and Al in the Ba precursor, Eu precursor and Al precursor is (3-x):x:4, wherein 0<x≤0.1.

[0028] Preferably, the purity of the Ba precursor, Eu precursor and Al precursor is not less than 99.5%.

[0029] Preferably, the temperature of the high-temperature solid-phase reaction is 1000-1400° C., the atmosphere is ammonia, the ammonia pressure is 10-20 MPa, and the time of the high-temperature solid-phase reaction is 4-10 h.

[0030] Another object of the present invention is to provide a white light LED device. The white light LED device comprises a high-efficiency narrow-band green nitride fluorescent material (corresponding to the chemical formula Ba 3-x Eu x Al4Si3N 10 , where 0<x≤0.1) and a purple LED chip that can produce 380~425 nm.

[0031] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0032] The present invention provides a high-efficiency narrow-band green nitride fluorescent material with a new crystal structure. The chemical formula of the fluorescent material is: Ba 3-x Eu x Al4Si3N 10, where 0<x≤0.1. The crystal structure of the fluorescent material corresponding to the matrix belongs to the orthorhombic system, and the space group is Immm. 2+ As an activator, under the excitation of 405 nm purple light, the main peak of the emission spectrum is between 515 and 545 nm, the half-width of the emission spectrum is in the range of 60 to 80 nm, and the quantum efficiency is greater than 80%, so that the fluorescent material can be used in white light LED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the emission spectrum of the material obtained in Comparative Example 1 under 405 nm excitation.

[0034] Figure 2 This is the emission spectrum of the material obtained in Comparative Example 3 under 405 nm excitation.

[0035] Figure 3 This is the emission spectrum of the material obtained in Comparative Example 5 under 405 nm excitation.

[0036] Figure 4 The X-ray diffraction pattern of the material obtained in Example 1 is shown in FIG.

[0037] Figure 5 This is a crystal structure diagram of the material obtained in Example 1.

[0038] Figure 6 The excitation and emission spectra of the material obtained in Example 1 are shown in FIG.

[0039] Figure 7 This is the emission spectrum of the material obtained in Example 6 under 405 nm excitation.

[0040] Figure 8 This is a spectrum diagram of the full-spectrum LED device obtained in Example 12. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0042] For ease of understanding of the present invention, the present invention enumerates embodiments as follows. Those skilled in the art should understand that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention. It should be noted that, in the absence of conflict, the embodiments in this application and the features described in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with embodiments.

[0043] The present invention provides a high-efficiency narrow-band green nitride fluorescent material, the chemical formula of which is:

[0044] Ba 3-x Eu xAl4Si3N 10

[0045] Among them, 0<x≤0.1.

[0046] In one embodiment of the present invention, the x is preferably 0.005; in one embodiment of the present invention, the x is preferably 0.01; in one embodiment of the present invention, the x is preferably 0.02; in one embodiment of the present invention, the x is preferably 0.03; in one embodiment of the present invention, the x is preferably 0.04; in one embodiment of the present invention, the x is preferably 0.05; in one embodiment of the present invention, the x is preferably 0.06; in one embodiment of the present invention, the x is preferably 0.07; in one embodiment of the present invention, the x is preferably 0.08; in one embodiment of the present invention, the x is preferably 0.09; in another embodiment of the present invention, the x is preferably 0.1.

[0047] The present invention also provides a method for preparing a high-efficiency narrow-band green nitride fluorescent material, the steps of which are as follows: mixing a Ba precursor, a Eu precursor and an Al precursor, and performing a high-temperature solid-phase reaction in an atmosphere with an ammonia pressure of 10 to 20 MPa to obtain a high-efficiency narrow-band green nitride fluorescent material.

[0048] In the above steps, in the Ba precursor, the molar ratio of Ba to Si is 1:1; in the Eu precursor, the molar ratio of Eu to Si is 1:1; and in the Ba precursor, the Eu precursor and the Al precursor, the molar ratio of Ba, Eu and Al is (3-x):x:4, wherein 0<x≤0.1.

[0049] In the above steps, the Ba precursor is selected from BaSi alloy; the Eu precursor is selected from EuSi alloy; and the Al precursor is selected from AlN.

[0050] The purity of the above-mentioned Ba precursor, Eu precursor and Al precursor is not less than 99.5%. The higher the purity, the less impurities in the obtained phosphor.

[0051] In the above steps, the temperature of the high-temperature solid phase is preferably 1000-1400°C, and the atmosphere is an ammonia atmosphere; in some embodiments provided by the present invention, the temperature of the high-temperature solid phase is preferably 1200°C; the gas pressure of the ammonia atmosphere is 10-20 MPa, and the gas pressure of the ammonia atmosphere is preferably 15 MPa in the present invention.

[0052] The high temperature solid phase time in the above steps is preferably 4 to 10 hours, more preferably 5 to 8 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 6 hours.

[0053] The high temperature solid phase reaction is preferably carried out in a high temperature furnace; after the reaction is carried out, the furnace is cooled to room temperature to obtain a high efficiency narrow band green nitride fluorescent material.

[0054] The embodiment of the present invention adopts a high temperature solid phase reaction to successfully prepare a high-efficiency narrow-band green nitride fluorescent material.

[0055] The present invention also provides a white light LED device. The white light LED device at least comprises a chemical formula of Ba 3- x Eu x Al4Si3N 10 (wherein 0<x≤0.1) represents a high-efficiency narrow-band green nitride fluorescent material and a purple LED chip that can generate light within 380~425 nm.

[0056] The specific production steps include: mixing a high-efficiency narrow-band green nitride fluorescent material with cyan fluorescent powder, yellow fluorescent powder, red fluorescent powder and epoxy resin, applying it to the surface of a purple LED chip that can produce 380-425 nm light, and then curing it at 150°C for 2 hours to obtain a white light LED device.

[0057] In order to further illustrate the present invention, a high-efficiency narrow-band green nitride fluorescent material and a preparation method thereof provided by the present invention are described in detail below in combination with examples. The reagents used in the following comparative examples and examples are all commercially available.

[0058] Comparative Example 1

[0059] The raw materials are BaSi and AlN, and the molar ratio of Ba to Al in BaSi and AlN is 3:4. After grinding and mixing the above raw materials, they are put into a crucible and sintered at 1200℃ for 6h in a high-temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba3Al4Si3N 10 materials.

[0060] The luminescence performance of the corresponding material in Comparative Example 1 was analyzed using a fluorescence spectrometer. The results are as follows: Figure 1 Since no possible luminescent center is doped in this comparative example, the comparative example 1 does not emit light.

[0061] Comparative Example 2

[0062] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.85:0.15:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.85 Eu0.15 Al4Si3N 10 materials.

[0063] The luminescence performance of the corresponding material in Comparative Example 2 was analyzed using a fluorescence spectrometer. The results show that the main peak of the emission spectrum of the material obtained in Comparative Example 2 is located at 562 nm, and the half-width of the emission spectrum is 91 nm. The quantum efficiency of the material corresponding to Comparative Example 2 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in Comparative Example 2 is 20.4%, which is low. Specific data are shown in Table 1. Although the material obtained in Comparative Example 2 is a green luminescent material, due to the high concentration of Eu doping, the material obtained in Comparative Example 2 undergoes concentration quenching effect, and its luminescence intensity and quantum efficiency are low.

[0064] That is, Comparative Example 2 has no possibility of being applied to white light LED devices (packages).

[0065] Comparative Example 3

[0066] The raw materials are BaSi, SrSi, EuSi and AlN. The molar ratio of Ba, Sr, Eu and Al in BaSi, SrSi, EuSi and AlN is 1.95:1:0.05:4. After grinding and mixing, the above raw materials are put into a crucible, sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere, and cooled to room temperature with the furnace to obtain a theoretical chemical composition of Ba 1.95 S E 0.05 Al4Si3N 10 materials.

[0067] The luminescence performance of the corresponding materials in Comparative Example 3 was analyzed using a fluorescence spectrometer. The results are as follows: Figure 2 As shown. Since Ba is partially replaced by Sr, the main peak of the emission spectrum of the material obtained in Comparative Example 3 is located at 593 nm, which is orange light, not green light; the half-width of the emission spectrum is 102 nm, and the half-width of the emission spectrum is relatively wide. The quantum efficiency of the material corresponding to Comparative Example 3 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in Comparative Example 3 is 10.7%, which is low. See Table 1 for specific data. It can be seen that when Sr replaces Ba, the luminous intensity and quantum efficiency of the obtained luminescent material will be too low, and it will not have the value of commercial application.

[0068] That is, Comparative Example 3 is an orange luminescent material, rather than a highly efficient narrow-band green luminescent material, and its luminous intensity is too low to be applicable to white light LED devices (packages).

[0069] Comparative Example 4

[0070] The raw materials are Ba3N2, Eu3N2, AlN and Si3N4. The molar ratio of Ba, Eu, Al and Si in Ba3N2, Eu3N2, AlN and Si3N4 is 2.95:0.05:4:3. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. Then, the theoretical chemical composition is Ba 2.95 Eu 0.05 Al4Si3N 10 materials.

[0071] The luminescence performance of the corresponding material in Comparative Example 4 was analyzed using a fluorescence spectrometer. The results showed that the main peak of the emission spectrum of the material obtained in Comparative Example 4 was located at 532 nm, and the half-width of the emission spectrum was 70 nm. The quantum efficiency of the material corresponding to Comparative Example 4 was tested using a quantum efficiency tester. The results showed that the quantum efficiency of the material obtained in Comparative Example 4 was 11.9%, which was a low value. See Table 1 for specific data. An X-ray diffractometer was used to perform X-ray analysis on the material obtained in Comparative Example 4. The results showed that there was a partial BaSiN2 impurity phase in the obtained material. That is, although the most reliable all-nitride raw material was used to synthesize the nitride fluorescent material, the target pure phase could not be obtained due to the presence of side reactions. Although the material obtained in Comparative Example 4 is a green luminescent material, its luminescence intensity and quantum efficiency are low due to the presence of impurities.

[0072] That is, Comparative Example 4 has no possibility of being applied to white light LED devices (packages).

[0073] Comparative Example 5

[0074] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.95:0.05:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under a 15MPa nitrogen atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.95 Eu 0.05 Al4Si3N 10 materials.

[0075] The luminescence performance of the corresponding materials in Comparative Example 5 was analyzed using a fluorescence spectrometer. The results are as follows: Figure 3As shown. The results show that the main peak of the emission spectrum of the material obtained in Comparative Example 5 is located at 531 nm, and the half-width of the emission spectrum is 68 nm. The quantum efficiency of the material corresponding to Comparative Example 5 was tested using a quantum efficiency tester. Since the atmosphere is a nitrogen atmosphere, the reducing ability is worse than that of ammonia. The results show that the quantum efficiency of the material obtained in Comparative Example 5 is 16.6%, which is low. See Table 1 for specific data. Although the material obtained in Comparative Example 5 is a green luminescent material, its luminescence intensity and quantum efficiency are low due to the lack of selection of a suitable reaction atmosphere.

[0076] That is, Comparative Example 5 has no possibility of being applied to white light LED devices (packages).

[0077] Example 1

[0078] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.995:0.005:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.995 Eu 0.005 Al4Si3N 10 materials.

[0079] The structure of the material obtained in Example 1 was analyzed by X-ray diffraction using an X-ray diffractometer, and the diffraction pattern was as follows: Figure 4 As shown. By searching and comparing the powder structure database, its diffraction data is completely different from the diffraction patterns of the currently known nitride fluorescent materials, which shows that the material obtained in Example 1 is a nitride fluorescent material with a completely new structure. Since the alloy is selected as the raw material instead of all nitride powder, the obtained material does not contain obvious impurities. Through single crystal diffraction analysis, combined with the data of powder structure refinement, it is shown that the crystal structure of the material (matrix) belongs to the orthorhombic system, the space group is Immm, Figure 5 The crystal structure of the material (matrix) is given. The corresponding phosphor in Example 1 is analyzed by fluorescence spectrometer to obtain its excitation and emission spectra, as shown in FIG. Figure 6 As shown. The material can absorb ultraviolet to blue light. Under 405 nm violet light excitation, the main peak of the emission spectrum is located at 515 nm, and the half-height width of the emission spectrum is 60 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its value was 82.3%, as shown in Table 1. The extremely high quantum efficiency value indicates that the material has extremely high packaging practical value.

[0080] It can be seen that Example 1 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0081] Example 2

[0082] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.99:0.01:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.99 Eu 0.01 Al4Si3N 10 materials.

[0083] The structure of the material obtained in Example 2 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 2 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 2 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 518 nm, and the half-width of the emission spectrum is 62 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 83.6%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0084] It can be seen that Example 2 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0085] Example 3

[0086] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.98:0.02:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.98 Eu 0.02 Al4Si3N 10 materials.

[0087] The structure of the material obtained in Example 3 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 3 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 3 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 522 nm, and the half-width of the emission spectrum is 65 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 88.5%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0088] It can be seen that Example 3 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of this high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0089] Example 4

[0090] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.97:0.03:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.97 Eu 0.03 Al4Si3N 10 materials.

[0091] The structure of the material obtained in Example 4 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 4 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 4 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 525 nm, and the half-height width of the emission spectrum is 66 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 87.1%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0092] It can be seen that Example 4 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0093] Example 5

[0094] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.96:0.04:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.96 Eu 0.04 Al4Si3N 10 materials.

[0095] The structure of the material obtained in Example 5 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 5 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 5 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 527 nm, and the half-height width of the emission spectrum is 68 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 88.2%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0096] It can be seen that Example 5 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0097] Example 6

[0098] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.95:0.05:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.95 Eu 0.05 Al4Si3N 10 materials.

[0099] The structure of the material obtained in Example 6 was analyzed by X-ray diffraction using an X-ray diffractometer. The results showed that the crystal structure of the obtained material was the same as that of Example 1. The corresponding phosphor in Example 6 was analyzed by a fluorescence spectrometer. The results are as follows: Figure 7As shown, it is shown that the material obtained in Example 6 can absorb ultraviolet to blue light. Under 405 nm violet light excitation, the main peak of the emission spectrum is located at 530 nm, and the half-height width of the emission spectrum is 69 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its value was 93.9%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high packaging practical value.

[0100] It can be seen that Example 6 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of this high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0101] Example 7

[0102] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.94:0.06:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.94 Eu 0.06 Al4Si3N 10 materials.

[0103] The structure of the material obtained in Example 7 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 7 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 7 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 535 nm, and the half-width of the emission spectrum is 72 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 90.7%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0104] It can be seen that Example 7 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of this high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0105] Example 8

[0106] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.93:0.07:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.93 Eu 0.07 Al4Si3N 10 materials.

[0107] The structure of the material obtained in Example 8 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 8 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 8 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 537 nm, and the half-height width of the emission spectrum is 75 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 83.4%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0108] It can be seen that Example 8 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of this high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0109] Example 9

[0110] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.92:0.08:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.92 Eu 0.08 Al4Si3N 10 materials.

[0111] The structure of the material obtained in Example 9 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 9 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 9 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 539 nm, and the half-width of the emission spectrum is 77 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 86.9%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0112] It can be seen that Example 9 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of this high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0113] Example 10

[0114] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.91:0.09:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.91 Eu 0.09 Al4Si3N 10 materials.

[0115] The structure of the material obtained in Example 10 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 10 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 10 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 540 nm, and the half-width of the emission spectrum is 79 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 88.1%, as shown in Table 1. The quantum efficiency value of this fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0116] It can be seen that Example 10 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of this high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0117] Embodiment 11

[0118] The raw materials are BaSi, EuSi and AlN. The molar ratio of Ba, Eu and Al in BaSi, EuSi and AlN is 2.9:0.1:4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1200℃ for 6h in a high temperature furnace under 15MPa ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba 2.9 Eu 0.1 Al4Si3N 10 materials.

[0119] The structure of the material obtained in Example 11 was analyzed by X-ray diffraction using an X-ray diffractometer. The results show that the crystal structure of the obtained material is the same as that in Example 1. The corresponding phosphor in Example 11 was analyzed using a fluorescence spectrometer. The results show that the material obtained in Example 11 can absorb ultraviolet to blue light, and under the excitation of 405 nm violet light, the main peak of the emission spectrum is located at 545 nm, and the half-width of the emission spectrum is 80 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and the value was 80.2%, as shown in Table 1. The quantum efficiency value of the fluorescent material is extremely high, indicating that the material has extremely high practical value for packaging.

[0120] It can be seen that Example 11 is a high-efficiency narrow-band green nitride fluorescent material. Under the excitation of 405 nm violet light, the main peak of the emission spectrum of this high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is in the range of 60-80 nm, the quantum efficiency is greater than 80%, and it can be used for white light LED device packaging.

[0121] Table 1 Luminescent properties of materials corresponding to comparative examples and examples

[0122]

[0123] Example 12

[0124] Select BaSi2O2N2:Eu cyan phosphor, BaSi2O2N2 synthesized in Example 6 2.95 Eu 0.05 Al4Si3N 10 Green phosphor, Y3Al5O 12 :Ce yellow phosphor and CaAlSiN3:Eu red phosphor are mixed with epoxy resin in a mass ratio of 1:2.55:0.52:0.36:12, and the mixture is coated on a purple LED with a main peak of emission spectrum at 410 nm, encapsulated, and then cured at 150°C for 2h to obtain a white light LED device with a color rendering index of 93.9. The spectrum of the device is shown in Figure 8 shown.

[0125] The above embodiments are only used to illustrate the implementation methods of the present invention and to explain the technical features of the present invention, and are not used to limit the protection scope of the present invention. Any changes or equivalent arrangements that can be easily completed by a person familiar with this technology belong to the scope claimed by the present invention, and the scope of protection of the present invention shall be subject to the claims.

Claims

1. A high-efficiency narrow-band green nitride fluorescent material, characterized by: The chemical formula of the high-efficiency narrow-band green nitride fluorescent material is Ba 3-x Eu x Al4Si3N 10 , wherein 0<x≤0.1; under the excitation of 405 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band green nitride fluorescent material is located at 515-545 nm, the half-width of the emission spectrum is 60-80 nm, and the quantum efficiency is >80%.

2. A high-efficiency narrow-band green nitride fluorescent material as claimed in claim 1, characterized in that: The x is 0.

05.

3. A method for preparing a high-efficiency narrow-band green nitride fluorescent material according to any one of claims 1 to 2, characterized in that: A Ba precursor, a Eu precursor and an Al precursor are mixed, and a high-temperature solid-phase reaction is carried out in an atmosphere with an ammonia pressure of 10 to 20 MPa to obtain the high-efficiency narrow-band green nitride fluorescent material; wherein the Ba precursor is selected from BaSi alloy, the Eu precursor is selected from EuSi alloy, and the Al precursor is selected from AlN.

4. The method for preparing a high-efficiency narrow-band green nitride fluorescent material according to claim 3, characterized in that: In the Ba precursor, the molar ratio of Ba to Si is 1:

1.

5. The method for preparing a high-efficiency narrow-band green nitride fluorescent material according to claim 3, characterized in that: In the Eu precursor, the molar ratio of Eu to Si is 1:

1.

6. The method for preparing a high-efficiency narrow-band green nitride fluorescent material according to claim 3, characterized in that: The molar ratio of Ba, Eu and Al in the Ba precursor, the Eu precursor and the Al precursor is (3-x):x:4, wherein 0<x≤0.

1.

7. The method for preparing a high-efficiency narrow-band green nitride fluorescent material according to claim 3, characterized in that: The temperature of the high temperature solid phase reaction is 1000-1400° C., and the time of the high temperature solid phase reaction is 4-10 hours.

8. Use of a high-efficiency narrow-band green nitride fluorescent material according to any one of claims 1 to 2 or a high-efficiency narrow-band green nitride fluorescent material prepared by the preparation method according to any one of claims 3 to 7, characterized in that: Used to prepare white light LED devices.

9. A white light LED device, characterized in that: It comprises a high-efficiency narrow-band green nitride fluorescent material as described in any one of claims 1 to 2 or a high-efficiency narrow-band green nitride fluorescent material obtained by the preparation method of any one of claims 3 to 7.

10. A white light LED device as claimed in claim 9, characterized in that: It also includes purple LED chips with a peak emission wavelength between 380 and 425 nm.

Citation Information

Patent Citations

  • Small-particle-size nitride narrow-band green fluorescent powder and preparation method thereof

    CN115093851A

  • Nitrogen oxide narrow-band green fluorescent material, preparation method and device

    CN116590004A

  • Phosphor, method for producing same, light-emitting device, and image display apparatus

    US20160060518A1